Targeting Localized Immune Suppression Within the Tumor Through Repeat Cycles of Immune Cell-oncolytic Virus Combination Therapy - Thorne, Stephen H (Nature Publishing Group, 2010)
A major limitation to the use of immunotherapy in the treatment of cancer has been the localized immune suppressive environment within the tumor. Although there is evidence that tumor-selective (oncolytic) viruses may help to overcome this immune suppression, a primary limitation to their use has been limited systemic delivery potential, especially in the face of antiviral immunity. We recently demonstrated that tumor-trafficking immune cells can efficiently deliver oncolytic viral therapies to their tumor targets. These cells act as both a therapeutic agent and also a carrier vehicle for the oncolytic virus. Here, we demonstrate that such delivery is also possible in the face of pre-existing antiviral immunity, so overcoming the limited systemic delivery of naked, cell-free virus. It was also found that treatment of previously immunized mice or repeat treatments leading to immunization resulted in a switch from a primarily oncolytic to an immunotherapeutic mechanism of action. Furthermore, repeat cycles of treatment with combination immune cell-viral therapy resulted in increased tumor infiltration of effector T-cells and a general reduction in the levels of known immune suppressive lymphocyte populations. This therefore represents a novel and effective means to overcome localized immune suppression within the tumor micoenvironment.